A Comparison Among Different Parameters for the Design of a Photovoltaic/Thermal System Using Computational Fluid Dynamics - Salami, P.; Ajabshirchi, Y.; Abdollahpoor, S.; Behfar, H. (Engineering, Technology & Applied Science Research, 2016)
The purpose of this paper is to compare several fins, duct height, and velocity magnitudes to acquire a PhotoVoltaic/Thermal system designed through Computational Fluid Dynamics. Simulation of different fins (rectangular, trapezoidal, curved, and pin) with different distances among fins is performed in Fluent software. The parameters such as duct height (4, 6, 8, and 10 centimeters) and velocity magnitudes (0.5, 1, 2, and 3 m/s) are also simulated. According to the results the highest cell temperature was 51°C at 0.5 m/s, while the best result was 33°C achieved with 4 cm duct height, rectangular fin and 3 m/s velocity magnitude. The findings suggest that the maximum cell temperature at the rate of 0.5 m/s is 51 °C, whereas temperature conducive to the best outputs is 33 °C. Differences among the cell temperatures through the various duct and the different fin types were significant at 1% level, also velocity magnitude would be cardinal at 1% level. A logarithmic regression model has been proposed to getting the cell temperature estimated by velocity magnitude.